(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Morphological Variations of the Vermiform Appendix and Their Clinical Relevance addresses a clinically relevant and measurable question in biomedical science. Methods: This observational anatomical study of cadaveric and operative specimens included 86 specimens and used standardized measurements, predefined eligibility criteria and appropriate statistical analysis. Results: The retrocaecal position was most common (47.7%), followed by pelvic (25.6%), subcaecal (12.8%), pre-ileal (8.1%) and post-ileal positions (5.8%). Mean appendiceal length was 7.8 ± 2.1 cm. Long appendices (>9 cm) were more often pelvic or post-ileal (p=0.018). A fully extending mesoappendix was seen in 62.8% specimens. Conclusion: Retrocaecal and pelvic positions were the most common appendiceal configurations, with clinically relevant variation in length and mesoappendix extent. Awareness of these patterns can improve recognition of atypical appendicitis and assist operative localization.